Renal hypokalemic paralysis: A rare manifestation of Sjogren's syndrome - U Punitha Gnana Selvi; Kamatchi Diravidamani; S Priyanka Devi Sekar; Keerthana Sekar (Wolters Kluwer Medknow Publications, 2016)
Sjögren's syndrome (SS) is typically associated with a lymphocytic, and plasmacytic infiltrate in the salivary, parotid, and lacrimal glands, leading to a sicca syndrome. This immune process can also affect nonexocrine organs, including the kidneys, producing an interstitial nephritis and defects in tubular function. Renal tubular acidosis develops in a large population of patients with SS, but most of the subjects are asymptomatic. In rare cases, hypokalemic paralysis becomes the primary presenting symptom. In this article, we report such a patient with acute paresis of skeletal muscles later diagnosed to be SS.